How volunteered geographic information can be integrated into emergency management practice? First lessons learned from an urban fire simulation in the city of Coimbra - Albuquerque, João Porto de (2016)
In the past few years, volunteered geographic information (VGI) has emerged as a new resource for improving the management of emergencies. Despite the growing body of research dedicated to the use of VGI in crisis management, studies are still needed that systematically investigate the incorporation of VGI into practical emergency management. To fill this gap, this paper proposes a research design for investigating and planning the incorporation of VGI into work practices and decision-making of emergency agencies by means of simulation exercises. Furthermore, first lessons are drawn from a field study performed within a simulation exercise of an urban fire in Coimbra, Portugal, implemented together with local civil protection agents. Emergency management practitioners identified a high potential in the pictures taken in-situ by volunteers for improving situational awareness and supporting decision-making. They also pointed out to challenges associated to processing VGI and filtering high-value information in real-time.